Soil and plant responses to pyrogenic organic matter: carbon stability and symbiotic patterns. - SAGRILO, E. (2014)
Soil amendment with pyrogenic organic matter (PyOM) can sequester carbon, increase mutualistic root symbioses with arbuscular mycorrhizal fungi and nitrogen-fixing rhizobia, and hence improve crop yield. However, there is still a gap in our knowledge about the effects of PyOM over longer temporal scales, especially in field experiments that last longer than one cropping cycle. This thesis aims to study interactions between PyOM and soil organic carbon (SOC) and symbiotic patterns in soybean (Glycine max) under tropical field conditions in a sandy ferralsol in northeast Brazil.